Adaptive work in the health care response to domestic violence in Palestine. (30th September 2020) - Bacchus, L; Alkaiyat, A; Shaheen, A; Alkhayyat, A; Od, H; Halaseh, R; Feder, G; Sandouka, R; Colombini, M
Abstract: Background: A health system response to domestic violence against women is a global priority. However, little is known about whether or how they work in LMICs where there are greater structural barriers. HERA (HEalthcare Responding to violence and Abuse) aimed to strengthen the primary healthcare response to domestic violence in the West Bank of Palestine. Methods: The sample for the qualitative study was 18 participants at two primary health care clinics and included five women, nine primary health care providers, two gender-based violence focal points and two domestic violence trainers. Data were analysed using thematic analysis drawing an Extended Normalisation Process Theory (ENPT) and feminist scholarship. We collected data on identification and referral of domestic violence cases. Results: HERA interacted with political, sociocultural and economic aspects of the context, creating a degree of unpredictability and uncertainty in working of the intervention. The political occupation restricted women's movement and access to support services, whilst the concomitant lack of police protection left providers and women feeling exposed to acts of family retaliation. This was interwoven with cultural values that influenced participants' choices as they negotiated normative structures that reinforce violence against women. Participants engaged in adaptive work to negotiate these challenges and ensure that implementation was safe and workable within a context of constraints. Participant narratives highlight the use of subterfuge, hidden forms of agency and governing behaviours (of self and others) to ensure the safety of all involved during implementation. Conclusions: The findings have implications for how HERA can be sustained in the long-term, particularly with regards to the provision of support for women. Support at all levels within the health system is needed to enable change and strengthen the response to violence against women. Key messages: Health care providers and women worked with and around contextual constraints. The transformation of the clinic case manager role is an emergent feature of HERA. Extended Normalisation Process Theory helped to articulate nuances about intervention-context interactions.